2021
DOI: 10.3390/cryst11111307
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mechanical Properties and Pore Structure of Hybrid Fiber Reinforced Rubber Concrete

Abstract: In this work, to reduce the probability of brittle failure in the support structure of deeply buried high-stress soft rock roadways, hybrid-fiber reinforced rubber concrete (HFRRC) was investigated using the orthogonal test, and the effects of various factors on the performance were studied. The mechanical properties, pore structure, and microstructure of rubber concrete reinforced by basalt fiber (BF) and polyvinyl alcohol fiber (PF) were studied from macroscale, mesoscale, and microscale perspectives. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Deng Fengqiang et al [38] found through experiments that the reinforcement effects of polypropylene fibre (PF) on the toughness and crack resistance of plain concrete are more pronounced than those on high-strength concrete. Liu Yushan [39] demonstrated through experiments that basalt fibre (BF) and polyvinyl alcohol fibre (PF) can enhance and fortify rubber concrete, impacting the mechanical properties, pore structure, and microstructure. According to experiments conducted by Fu Qiang and his team [40], inclusions of BF and PF in concrete can boost its flexural strength and enhance the tortuosity of crack propagation, ultimately improving its ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Deng Fengqiang et al [38] found through experiments that the reinforcement effects of polypropylene fibre (PF) on the toughness and crack resistance of plain concrete are more pronounced than those on high-strength concrete. Liu Yushan [39] demonstrated through experiments that basalt fibre (BF) and polyvinyl alcohol fibre (PF) can enhance and fortify rubber concrete, impacting the mechanical properties, pore structure, and microstructure. According to experiments conducted by Fu Qiang and his team [40], inclusions of BF and PF in concrete can boost its flexural strength and enhance the tortuosity of crack propagation, ultimately improving its ductility.…”
Section: Introductionmentioning
confidence: 99%
“…CRC is a composite based on ordinary concrete that is formed by adding finer crumb rubber to replace some of the fine aggregate or larger crumb rubber to replace some of the coarse aggregate. Research has shown that CRC outperforms ordinary concrete in terms of energy absorption and consumption [ 13 , 14 ], fatigue resistance [ 15 ], reducing material brittle failure [ 16 ], deformation capacity [ 17 ], hindering crack development [ 18 ], durability [ 19 , 20 , 21 ], and thermal performance [ 22 ]. To reduce the degree of brittle failure of deep foundation pit support structures, the application of CRC to deep foundation pit support has been studied [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that CRC outperforms ordinary concrete in terms of energy absorption and consumption [ 13 , 14 ], fatigue resistance [ 15 ], reducing material brittle failure [ 16 ], deformation capacity [ 17 ], hindering crack development [ 18 ], durability [ 19 , 20 , 21 ], and thermal performance [ 22 ]. To reduce the degree of brittle failure of deep foundation pit support structures, the application of CRC to deep foundation pit support has been studied [ 16 ]. The addition of rubber powder has a positive impact on the durability of concrete and can effectively reduce the migration rate of chloride ions in the concrete [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical reinforcement technology not only improves the strength of soil but also greatly improves the physical and mechanical properties of soil, such as tensile and flexural strength, so it has been widely used. The commonly used soil reinforcement materials include cotton and hemp products [9,[14][15][16], geotextile [17][18][19], polypropylene fiber [20][21][22][23][24][25][26], glass fiber [27], basalt fiber [27][28][29], and steel fiber [7,25]. The natural tensile properties, surface friction properties, and good dispersion of these materials make them connected with the cementitious substances produced by the hydration reaction of cement in a network 2 of 19 structure, which enhances the bonding force of the contact interface and improves the ability of soil to resist deformation.…”
Section: Introductionmentioning
confidence: 99%